Flexible layered cotton cellulose-based nanofibrous membranes for piezoelectric energy harvesting and self-powered sensing. (1st January 2022) - Wang, Leiyang; Cheng, Tao; Lian, Wangwei; Zhang, Mengxia; Lu, Bo; Dong, Binbin; Tan, Kunlun; Liu, Chuntai; Shen, Changyu
Abstract: Cellulose has attracted an increasing attention for piezoelectric energy harvesting. However, the limited piezoelectricity of natural cellulose constraints the applications. Therefore, we demonstrate the development of piezoelectric nanogenerators based on robust, durable layered membranes composed of cotton cellulose interfaced maleic-anhydride-grafted polyvinylidene fluoride (PVDF- g -MA) nanofibers. Exploiting polydopamine@BaTiO3 (pBT) nanoparticles as interlayer bridges, interlocked layer–layer interfaces that covalently bind component layers are constructed by a facile and scalable approach. As-obtained membranes exhibit significantly improved piezoelectricity with a maximum piezoelectric coefficient of 27.2 pC/N, power density of 1.72 μW/cm 2, and stability over 8000 cycles. Substantial enhancement in piezoelectricity over pristine cellulose is ascribed to the synergy of components and the localized stress concentration induced by pBT nanoparticles. The self-powered device could also be used to detect human physiological motions in different forms. Such cellulose-based membranes can be up-scaled to fabricate ecofriendly, flexible and durable energy harvesters and self-powered wearable sensors. Graphical abstract: Unlabelled Image